Genetic parameters affecting leg length, leg weakness, hip- and elbow conformation in domesticated dogs, in comparison with pigs - Ekenberg, Victoria (2015)
Genetic parameters for four leg conformation traits in dogs (Canis lupus familiaris) are in this literature review summarized to investigate whether selective breeding could be useful to improve purebred dogs´ health and welfare. The four traits are leg length, leg weakness, hip joint and elbow joint conformation. When summarized, the genetic parameters are compared with genetic parameters affecting in pigs (Sus scrofa). Of the four traits, hip and elbow conformations were mostly studied in dogs. However, these traits were not widely studied in pigs. In pigs the most studied trait was leg weakness. The trait leg length is studied in both species, however, these studies mainly focuses on causative genes and not genetic parameters. A positive correlation was found between hip and elbow joint conformation in dogs. In pigs, a steep and weak forearm pastern was associated with a worse elbow score, indicating that this should also be tested in dogs. In conclusion more research on correlations between these four traits and on leg length and leg weakness traits needs to be done in dogs. If this is done selective breeding can be used effectively to improve purebred dogs´ leg conformation and welfare. SAMMANFATTNING. Denna litteraturstudie sammanfattar genetiska parametrar för benkonformation hos hund (Canis lupus familiaris). Detta för att undersöka ifall selektiv avel är användbart till att förbättra hundars hälsa och välfärd med avseende på fyra ben konformationer; benlängd, bensvaghet, höftled och armbågsledskonformation. Summerade genetiska parametrarna hos hund jämförs sedan med genetiska parametrar hos gris (Sus scrofa). Av de fyra konformationerna så är höft och armbågsleds konformation mest studerade hos hund, dessa är inte lika utförligt studerade hos gris. På gris så är bensvaghet mest välstuderat. Benlängd finns studerat hos både gris och hund, dock är dessa studier huvudsakligen fokuserade på orsakande gener och inte genetiska parametrar. En positiv korrelation mellan höft och armbågsleder finns. Även en brant och svag karled hos gris har associerats till sämre armbågsled, detta indikerar att tester för detta bör göras även hos hund. Sammanfattningsvis så behövs det mer forskning om korrelationer mellan dessa egenskaper, även mer forskning om benlängd och bensvaghet behövs. Görs detta kan selektiv avel användas för att förbättra renrasiga hundars benkonformation och välfärd.